A polymorphism in the XPD gene predisposes to leukemic transformation and new nonmyeloid malignancies in essential thrombocythemia and polycythemia vera - Hernández-Boluda, Juan-Carlos; Pereira, Arturo; Cervantes, Francisco; Alvarez-Larrán, Alberto; Collado, María; Such, Esperanza; Arilla, M. Jesús; Boqué, Concepción; Xicoy, Blanca; Maffioli, Margherita; Bellosillo, Beatriz; Marugán, Isabel; et al. (Blood, 2012)
Patients with essential thrombocythemia (ET) and polycythemia vera (PV) have an increased incidence of acute myeloid leukemia and new nonhematologic malignancies compared with the general population. However, information on the factors determining the risk for such complications is limited. In the present study, we investigated whether constitutional genetic variations in DNA repair predispose to leukemic transformation and new nonmyeloid neoplasias in patients with ET and PV. Case-control studies for predisposition to both types of malignancies were nested in a cohort of 422 subjects diagnosed with ET or PV during the period 1973-2010 in several institutions in Spain. A total of 64 incidence cases of leukemia and 50 cases of primary nonmyeloid cancers were accrued. At conditional regression analysis, the Gln/Gln genotype in the XPD codon 751 showed the strongest association with both leukemic transformation (odds ratio [OR] = 4.9; 95% confidence interval [95% CI], 2.0-12) and development of nonmyeloid malignancies (OR = 4.2; 95% CI, 1.5-12). Additional predictive factors were exposure to cytoreductive agents for leukemic transformation (OR = 3.5; 95% CI, 2.0-6.2) and age for nonmyeloid malignancies (OR = 2.0; 95% CI, 1.4-2.8). These findings provide further evidence about the contribution of inherited genetic variations to the pathogenesis and clinical course of myeloproliferative neoplasms.